President McPhee, Roy E. Simpson, Joseph Loeb, and William L. Blair at a Legislative and Press Preview of Cal Poly's new Kellogg Unit near Pomona (1950)
President McPhee shows the Arabian twins, Calamyr and Calamyra, to Roy E. Simpson (right), State Superintendent of Public Instruction, Joseph Loeb (left), member of the State Board of Education, and William L. Blair, President of the State Board of Education, at a legislative and press preview of Cal Poly's new Kellogg Unit near Pomona, February 25, 1950.